The Incessant Strife between Tradition and Modernity in Manju Kapur’s Difficult Daughters - Lavanya, B. (International Journal of Psychosocial Rehabilitation, 2020)
Manju Kapur, one of the prominent Indian women writers writing in English, has published five novels till date. Her first three novels are Difficult Daughters, A Married Woman and Home. In her novels, she has shown her mastery in both style and technique. Kapur voices against the phallocentric culture and strongly detects the marginalization of women. She does not believe in describing her women characters as love-slaves or mere helpmates at home. In her novels she presumably mirrors her own feminist and feminine mind set. The novel Difficult Daughters brings to light the same kind of life and struggle of women wherever they are under the oppressive mechanism of a close society. Also, it presents an incessant strife between Tradition and Modernity and how the characters are involved in the ongoing fight. Her novel presents a situation in which a woman has to rise above her stature and get rightful and meaningful place in the society. Through the novel Difficult Daughters, Kapur wants to speak about the idea of independence with great narrative eloquence.